Examining Digital Technology for (Higher) Education through Action Research and Critical Discourse Analysis - Waghid, Z; Waghid, F (South African Journal of Higher Education, 2016)
The public understanding of scientific, economic, political and ethical issues is becoming increasingly important as students are confronted with socio-economic issues impacting their everyday lives. Grappling with these issues requires critical, deliberative and autonomous students. According to Wankle (2011, 7), the use of digital technology in education may serve as a catalyst for cultivating excitement, interaction and sharing in students. In this article, the authors, using two distinct research methodologies, argue that using Facebook as a digital technological methodology in (higher) education could provide a means of mediating and communicating in today’s modern society, so that (higher) educationists can engage with students both deliberatively and critically so as to enhance students’ understanding of current economic, political and cultural issues autonomously. The authors posit that the application of digital technology can be implemented successfully if students and (higher) educationists possess the capabilities to do so.